Rejected Syrians - Badalič, Vasja (Dve domovini, 2019)
The article analyses the practices used by Turkey, Jordan and Lebanon to prevent Syrians from exercising their right to seek and enjoy asylum. The article consists of two sections. The first section examines how all three host countries violated the principle of non-refoulement by employing a range of unlawful practices (e.g. border closures and "pushbacks", arbitrary detentions and deportations etc.). The second section examines how Lebanon resorted to practices that created circumstances for constructive refoulement of Syrian asylum seekers and refugees (e.g. shutting down the authority responsible for processing asylum claims, stripping Syrian refugees of their protected status etc.).
Keywords: begunci; constructive refoulement; človekove pravice; human rights; Jordan; Jordanija; Lebanon; Libanon; načelo nevračanja; posredno prisilno vračanje; principle of non-refoulement; refugees; sirski begunci; Syrian refugees; Turčija; Turkey